2015
DOI: 10.1007/s00395-015-0487-4
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Flt-1 links microvascular disease with heart failure in CKD

Abstract: Chronic kidney disease (CKD) is associated with an increased risk of heart failure (HF). Elevated plasma concentrations of soluble Flt-1 (sFlt-1) have been linked to cardiovascular disease in CKD patients, but whether sFlt-1 contributes to HF in CKD is still unknown. To provide evidence that concludes a pathophysiological role of sFlt-1 in CKD-associated HF, we measured plasma sFlt-1 concentrations in 586 patients with angiographically documented coronary artery disease and renal function classified according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…30 Di Marco et al also revealed that exogenous administration of sFlt-1 causes heart failure by reducing heart capillary density and myocardial blood flow, with interstitial fibrosis and mitochondrial damages in rats. 8 Importantly, angiogenic factors are considered to have an important role in the process of adaptive cardiac response to pressure overload. [31][32][33] These results suggest that higher than normal levels of sFlt-1 may result in adverse effects on cardiac function by binding and sequestering angiogenic factors, leading to impaired angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…30 Di Marco et al also revealed that exogenous administration of sFlt-1 causes heart failure by reducing heart capillary density and myocardial blood flow, with interstitial fibrosis and mitochondrial damages in rats. 8 Importantly, angiogenic factors are considered to have an important role in the process of adaptive cardiac response to pressure overload. [31][32][33] These results suggest that higher than normal levels of sFlt-1 may result in adverse effects on cardiac function by binding and sequestering angiogenic factors, leading to impaired angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In clinical settings, plasma levels of sFlt-1 are not only directly correlated with the severity of heart failure but also strongly associated with poor outcomes in patients with heart failure.…”
Section: Suppressed Production Of Soluble Fms-like Tyrosine Kinase-1 mentioning
confidence: 99%
See 3 more Smart Citations